The sorption dynamics of C3 hydrocarbons over carbon nanotubes - Onyestyák, György; Ötvös, Zsolt; Kiricsi, Imre; Rees, Lovat V. C. (Diffusion Fundamentals, 2005)
Carbon nanotubes obtained by the catalytic vapor deposition (CVD) method were purified by various procedures to obtain samples in pure and well-defined forms. The frequency response (FR) technique was employed to determine the sorption dynamics of C3-hydrocarbons in these samples. Two parallel sorption processes were found, characterized by different sorption capacities and time constants and were assigned to sorption on the convex and concave surfaces of the carbon tubes, respectively. Over a carbon nanotube sample at low coverage the mass transport is little influenced by the different chemical nature of the various C3 hydrocarbons. However the dynamic sorption properties of carbon nanotube preparations were shown to be strongly affected by the absence or presence of surface functional groups on the outer and inner surfaces of the tube walls. Different rate-determining mechanisms were observed for the samples functionalized to different extents.